Book Reviews - Lindsay, Robert; Grant, H. Roger; Frey, Marsha L.; Reilly, John T.; Marran, James F.; Enders, Victoria L.; Tate, Benjamin; Banner-Haley, Charles T.; Boland, Brian; Slater, Peter Gregg; et al. (Teaching History: A Journal of Methods, 1989)
Martin K. Sorge. The Other Price of Hitler’s War. German Military and Civilian Losses Resulting from World War II. Westport, CT: Greenwood Press, 1986. Pp. xx, 175. Cloth, 32.95; M. K. Dziewanowski. War At Any Price: World War II in Europe, 1939-1945. Englewood Cliffs, NJ: Prentice-Hall, 1987. Pp. xiv, 386. Paper, 25.67. Review by Lawrence S. Rines of Quincy Community College. David Goldfield. Promised Land: The South Since 1945. Arlington Heights, IL: Harlan Davidson, Inc., 1987. Pp. xiii, 262. Cloth, 19.95, Paper, 9.95; Alexander P. Lamis. The Two Party South. New York: Oxford University Press, 1984. Pp. x, 317. Cloth, 25.00; Paper, 8.95. Review by Ann W. Ellis of Kennesaw College. Walter J. Fraser, Jr., R. Frank Saunders, Jr., and Jon L. Wakelyn, eds. The Web of Southern Social Relations: Women, Family, and Education. Athens: University of Georgia Press, 1985. Pp. XVII, 257. Paper, 12.95. Review by Thomas F. Armstrong of Georgia College. William H. Pease and Jane H. Pease. The Web of Progress: Private Values and Public Styles in Boston and Charleston, 1828-1842. New York and Oxford: Oxford University Press, 1985. Pp. xiv, 334. Paper, 12.95. Review by Peter Gregg Slater of Mercy College. Stephen J. Lee. The European Dictatorships, 1918-1945. London and New York: Methuen, 1987. Pp. xv, 343. Cloth, 47.50; Paper, 15.95. Review by Brian Boland of Lockport Central High School, Lockport, IL. Todd Gitlin. The Sixties: Days of Hope, Days of Rage. New York: Bantam, 1987. Pp. 483. Cloth, 19.95; Maurice Isserman. IF I HAD A HAMMER... : The Death of the Old Left and the Birth of the New Left. New York: Basic Books, 1987. Pp. xx, 244. Cloth, 18.95. Review by Charles T. Banner-Haley of Martin Luther King, Jr. Center for Nonviolent Social Change, Inc. Donald Alexander Downs. Nazis in Skokie: Freedom, Community, and the First Amendment. Notre Dame IN: Notre Dame Press, 1985. Pp. 227. Paper, 9.95. Review by Benjamin Tate of Macon Junior College. Paul Preston, The Triumph of Democracy in Spain. London and New York: Methuen, 1986. Pp. 227. Cloth, 32.00. Review by Victoria L. Enders of Northern Arizona University. Robert B. Downs. Images of America: Travelers from Abroad in the New World. Urbana and Chicago: University of Illinois Press, 1987. Pp. 232. Cloth, 24.95. Review by James F. Marran of New Trier Township High School, Winnetka, IL. Joel H. Silbey. The Partisan Imperative: The Dynamics of American Politics Before the Civil War. New York and Oxford: Oxford University Press, 1985. Pp. viii, 234. Paper, 8.95. Review by John T. Reilly of Mount Saint Mary College. Barbara J. Howe, Dolores A. Fleming, Emory L. Kemp, and Ruth Ann Overbeck. Houses and Homes: Exploring Their History. Nashville: The American Association for State and Local History, 1987. Pp. xii, 168. Paper, 13.95; 11.95 to AASLH members. Review by Marsha L. Frey of Kansas State University. Thomas C. Cochran. Challenges to American Values: Society, Business and Religion. New York and Oxford: Oxford University Press, 1987. Pp. 147. Paper, 6.95. Review by H. Roger Grant of University of Akron. M.S. Anderson. Europe in the Eighteenth Century, 1713-1783. London and New York: Longman, 1987. Third Edition. Pp. xii, 539. Cloth, 34.95. Review by Robert Lindsay of the University of Montana.